THE USE OF GRAPHIC VISUALIZATION IN ENHANCING STUDENTS’ UNDERSTANDING OF INTEGRATION BY PARTS - Siti Asmah Mohamed; Fadzilawani Astifar Alias; Nurhafizah Ahmad; Muniroh Hamat (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the effectiveness of the LIATE Mnemonic Diagram as a visual instructional aid for improving students’ understanding and application of the Integration by Parts (IBP) technique in undergraduate calculus. A quantitative research design was employed, involving 75 students enrolled in a first-year calculus course at Universiti Teknologi MARA (UiTM). Participants completed a pre-test and post-test to assess their ability to select appropriate functions for u and dv, and to apply the IBP formula accurately. Following instruction using the LIATE Mnemonic Diagram, students demonstrated significant improvements in both function selection and overall problem-solving performance. Descriptive statistics and paired sample t-tests confirmed the statistical significance of these gains. The findings indicate that the LIATE Mnemonic Diagram supports students in reducing common errors and enhancing procedural fluency. This study contributes to mathematics education by providing empirical evidence on the instructional value of visual mnemonic tools in facilitating conceptual understanding and accuracy in integral calculus.